A Review of Advancements in Investigating MicroRNA Roles in Breast Cancer Bone Metastasis - Abidin, Ali Zainal; Aryandono, Teguh; Putranto, Ignatius Raden Endy Widya; Wahyuningsih, Arum Tri; Dewi, Dyah Laksmi (Trends in Sciences, 2025)
Breast cancer is among the most prevalent malignancies affecting women globally. Metastasis is a common clinical issue associated with a poor prognosis for breast cancer patients. Bones are one of the most common target organs for metastasis found in breast cancer patients, with a frequency of 70% in metastatic breast cancer. Dysregulation of microRNA (miRNA) is one of the critical molecular factors that mediates bone metastasis in breast cancer. miRNAs expressed by primary breast cancer tissue are known to shape the pre-metastatic bone microenvironment and cause osteolytic bone metastasis in breast cancer. Further investigation is required into the biological implications of alterations in miRNA expression during bone metastasis. In summary, recent advancements in understanding the role of miRNAs in breast cancer bone metastasis have explained the fundamental mechanisms of this process and introduced novel possibilities for improved diagnostic, prognostic, and therapeutic approaches. HIGHLIGHTS This review article focused comprehensively on critical roles of microRNAs in driving breast cancer bone metastasis. The role of various miRNAs in regulating key steps of bone metastasis, including pre-metastatic niche formation, cancer cell migration, and invasion. The potential of targeting miRNA pathways as novel therapeutic approaches for the prevention and treatment of bone metastasis in breast cancer. GRAPHICAL ABSTRACT